Museum Astronomi dengan Pendekatan Arsitektur Biomimikri di Makassar - Ismajaya, Muh. Aryanugraha; Said, Ratriana; Alfiah, Alfiah (TIMPALAJA : Architecture Student Journals, 2020)
Abstrak_Perancangan museum astronomi dengan pendekatan arsitektur biomimikri di Makassar bertujuan untuk menyediakan sarana wisata edukasi untuk mewadahi minat dan keingintahuan masyarakat tentang ilmu astronomi terkhusus di kota Makassar. Prinsip perancagan Museum Astronomi memperhatikan alam sekitar sehingga dapat menyesuaikan dengan alam tempat bangunan akan dibangun. Pada perancangan ini akan berfokus pada penerapan arsitektur biomimikri dengan menggunakan fasad kinetik yang dapat diatur menggunakan konfigurasi dari komputer. Kata Kunci: Museum; Astronomi; Perancangan, Gedung, Biomimikri. Abstract_The design of the Astronomy Museum with the Biomimicry Architecture design in Makassar offers a means of educational education to accommodate the interests and curiosity of the public about astronomy in particular in the City of Makassar. The Museum of Astronomy Design needs to pay attention to the natural surroundings so that it can adjust to nature where the building will be built. In this design, biomimicry architecture planning will be approved using a kinetic facade that can be set using a computer configuration. Keywords: Museum, Astronomy, Design, Building, Biomimicry.